Assessing drinking water quality and health risks of contaminants in the coastal areas of Cambodia. (23rd January 2023) - Sao, Vibol; Chey, Chan Oeurn; Sriv, Tharith; The, Noreaksatya; Phin, Samnang; Hoeng, Sophanith; Phan, Kongkea
Abstract: The present study aimed to assess the health risks of chemical contaminants of residents in the coastal areas of Cambodia through their drinking water pathways. Water was sampled from tube wells ( n = 22), dug wells ( n = 31), ponds ( n = 11), canals ( n = 12) and lakes ( n = 4) across the Cambodian coastal areas, and measured for the contaminants of health concern (As, Cu, Cr, Cd, F −, NO 2 -, NO 3 -, Pb, Escherichia coli and total coliform) and aesthetic quality following the United States Environmental Protection Agency (USEPA) and standard methods. Analytical results reveal that 9.1% of tube wells and 9.7% of dug wells contained As > 0.01 mg/L. Appropriately, 22.7% of tube wells and 32.3% of dug wells contained Fe > 0.3 mg/L while 100% of tube wells and 80.6% of dug wells contained Mn > 0.1 mg/L. Health risk assessment found that the hazard quotient (HQ) > 1 for children and women. Additionally, the lifetime cancer risk (LCR) was found >1 × 10 −4 for As in Cambodian coastal areas. Therefore, a monitoring programme and appropriate treatment to remove contaminants like arsenic, cadmium and fluoride would be required to ensure a safe drinking water supply to Cambodian coastal residents. HIGHLIGHTS: Both total coliform and E. coli were found in the tube well, dug well, ponds, canals and lakes while the Cambodian Drinking Water Quality Standard for total coliform and E. coli is not detectable per 100 mL. Health risk assessment revealed that for children and women residing in the coastal areas of Cambodia had HQ > 1. Men, women and children residing in the coastal areas of Cambodia are exposed to carcinogenic risk of As through drinking water pathways. Graphical Abstract